Analisis Dinamika Kepemimpinan dalam Menghadapi Konflik Internal di SMA Negeri 1 Silangkitang - Amin Harahap; Bisma Salsa Fitri Lubis; Tri Rahmawati (MAN 4 Kota Pekanbaru, 2026)
This study investigates the leadership of the principal in managing internal conflicts within school organizations. Internal conflict is an inherent aspect of organizational dynamics that requires flexible, communicative, and participatory leadership. At the senior high school level, conflicts extend beyond structural issues to include interpersonal relationships, organizational communication, and role distribution. This research was conducted at SMA Negeri 1 Silangkitang using a qualitative approach with a case study design. Data were collected through documentation and observation to obtain a contextual understanding of conflict dynamics and leadership practices. Data analysis was carried out descriptively through data reduction, data display, and conclusion drawing. The findings indicate that internal conflicts manifest as communication conflicts, task distribution conflicts, conflicts of interest, and interpersonal relationship conflicts. The study concludes that dialogical leadership integrating relational and structural approaches is essential for fostering a conducive work environment and strengthening educational governance.